Comprehensive Proteomic Characterization of the Pectoralis Major at Three Chronological Ages in Beijing-You Chicken - Zhang, Jian; Cao, Jing; Geng, Ailian; Wang, Haihong; Chu, Qin; Yang, Linbing; Yan, Zhixun; Zhang, Xiaoyue; Zhang, Yao; Dai, Jie; Liu, Huagui (Frontiers in Physiology, 2021)
Chronological age is one of the important factors influencing muscle development and meat quality in chickens. To evaluate the protein expression profiles during skeletal muscle development, we performed a tandem mass tag (TMT)-based quantitative proteomic strategy in pectoralis major (breast muscle) of Beijing-You chicken (BYC) at the chronological age of 90, 120 and 150 days. Each chronological age contained 3 pooling samples or 15 birds (5 birds per pooling sample). A total of 1,413 proteins were identified in chicken breast muscle with FDR <1% and 197 of them were differentially expressed (fold change ≥ 1.2 or ≤ 0.83 and p < 0.05). There were 110 up- and 71 down-regulated proteins in 120 d vs. 90 d group, 13 up- and 10 down-regulated proteins in 150 d vs. 120 d group. The proteomic profiles of BYC at 120 d were very similar to those at 150 d and highly different from those at 90 d, suggesting that 120 d might be an important chronological age for BYC. Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses indicated that these differentially expressed proteins were mainly involved in the pathway of glycolysis/gluconeogenesis, adrenergic signaling in cardiomyocytes, focal adhesion, oocyte meiosis and phagosome. Furthermore, some DEPs were quantified using parallel reaction monitoring (PRM) to validate the results from TMT analysis. In summary, these results provided some candidate protein-coding genes for further functional validation and contribute to a comprehensive understanding of muscle development and age-dependent meat quality regulation by proteins in chickens.